Humour in Chinese life and culture : resistance and control in modern times - Davis, Jessica Milner; Chey, Jocelyn Valerie (Hong Kong University Press, 2013)
This book investigates the use of humor in the public sphere and in personal life in China. The contributors cover modern and contemporary forms -- comic films and novels, cartooning, pop-songs, Internet jokes, and humor in advertising and education. The second of two multidisciplinary volumes designed for the general reader as well as academic audiences, the book explores the relationship between political control and popular expression of humor, including the mutual exchange of comic stereotypes between China and Japan, and draws out important methodological implications for psychological and cross-cultural studies of humor.